The role of circulating mesenchymal progenitor cells (fibrocytes) in the pathogenesis of fibrotic disorders - Keeley, Ellen; Mehrad, Borna; Strieter, Robert M. (Thrombosis and Haemostasis, 2009)
Fibrocytes are bone marrow-derived mesenchymal progenitor cells that express markers of leukocytes, haematopoietic progenitor cells, and fibroblasts. They play a pivotal role in tissue remodelling and fibrosis in both physiologic and pathologic settings. Fibrocytes are unique in that they are capable of differentiating into fibroblasts and myofibroblasts, as well as adipocytes. In this review we will present data supporting the critical role they play in the pathogenesis of chronic inflammatory fibrotic diseases of the lungs, heart and vasculature.
Keywords: Chemokines; collagens; wound healing